Kinematics and kinetics analyses on the effect of foot orthotic during a step-down movement - Lee, Kee Hao. (2008)
The project included the construction and validation of a new methodology for the purpose of this study and actual kinematics and kinetics analyses on the effect of a custom-molded semi-rigid full contact foot orthotic using a step-down movement.